The Effect of Using the Writing Processes Approach in Enhancing the Writing Skills of Essay and Thought among Female Class Teacher Students at Yarmouk University - Khodair, Raed (Jordan Journal of Educational Sciences, 2016)
This study aimed at investigating the effect of using the writing processes approach in enhancing the writing skills among the Female Class Teacher students at Yarmouk University. The subjects of the study consisted of (56) female students enrolled in "Expressive Writing Applications for First Grades" Course in the second semester of the academic year of 2013-2014, were selected by available method. In the beginning of the semester the students were pretested in writing essay and thought. Participants students were trained through group writing workshops on the writing processes approach, which entailed five stages namely: pre-writing, first draft writing, revision, editing, and publishing. The writing topics, which students received training on, were diverse and included essays, thoughts, short stories, and personal letters. The training went on for eight weeks with two sessions per week where each session was carried on for one hour at least. The posttest analysis results of the students' writings displayed overt qualitative and substantial improvement in their writing skills. Moreover, there were statistically significant difference in the writing skills of essay and thought due to the type of writing in the favor of the thought